Ultrasound-Guided Percutaneous Balloon Aortic Valvuloplasty for Aortic Stenosis - Yedan Li; Kunjing Pang; Yao Liu; Muzi Li; Hao Wang (Journal of Interventional Cardiology)
Percutaneous balloon aortic valvuloplasty (PBAV), which is used to treat symptomatic aortic stenosis, requires ionizing radiation and contrast agent for imaging guidance. The aim of the study is to evaluate the feasibility and effectiveness of ultrasound-guided PBAV in patients with aortic stenosis. This case series included 30 patients (14 males; mean age, 61.5 ± 4.5 years) with moderate/severe aortic stenosis treated with ultrasound-guided PBAV at the Ultrasound Department, Fuwai Hospital, Beijing, China, between January 2016 and July 2019. Cardiac function (New York Heart Association grade) was assessed before PBAV and 1 month after the procedure. Aortic peak jet velocity, aortic valve orifice area (AVA), mean transvalvular pressure gradient (MTPG), left ventricular end-diastolic diameter (LVDD), left ventricular ejection fraction (LVEF), and left ventricular end-systolic diameter (LVESD) were determined before and immediately after PBAV using Doppler echocardiography. Preprocedural cardiac function was grade I in 3 cases, grade II in 9 cases, grade III in 10 cases, and grade IV in 8 cases. Postprocedural cardiac function was grade I in 22 cases, grade II in 4 cases, and grade III in 4 cases, suggesting that cardiac function was improved by PBAV. Ultrasound-guided PBAV resulted in significant improvements (P<0.05) in aortic peak jet velocity (3.68 ± 0.811 m/s vs. 4.79 ± 0.63 m/s), MTPG (33.77 ± 13.85 mmHg vs. 54.54 ± 13.81 mmHg), AVA (1.96 ± 0.25 cm2 vs. 0.98 ± 0.12 cm2), LVEDD (51.90 ± 3.21 mm vs. 65.60 ± 6.81 mm), LVEF (63.46 ± 11.29% vs. 56.31 ± 11.04%), and LVESD (35.50 2.62 mm vs. 45.20 ± 2.42 mm). Ultrasound-guided PBAV is feasible and achieves good short-term effects in patients with aortic stenosis.